2018
DOI: 10.1111/clr.13288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of advanced age and/or systemic medical conditions on dental implant survival: A systematic review and meta‐analysis

Abstract: Objectives: This review evaluated implant survival in geriatric patients (≥75 years) and/or the impact of systemic medical conditions. Materials and Methods: Systematic literature searches were performed to identify studies reporting on geriatric subjects with dental implants and on implant patients who had any of the seven most common systematic conditions among geriatric patients. Meta-analyses were performed on the postloading implant survival rates. The impact of systemic medical conditions and their respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 87 publications
4
118
1
8
Order By: Relevance
“…Several more recent studies have concluded that diabetic patients may have similar positive outcomes to those found with healthy, nondiabetic patients . Their findings have led to a more rigorous and open scientific investigation of the impact systemic factors have on implant therapy success.…”
Section: The Impact Of Glycemic Control On Successful Implant Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Several more recent studies have concluded that diabetic patients may have similar positive outcomes to those found with healthy, nondiabetic patients . Their findings have led to a more rigorous and open scientific investigation of the impact systemic factors have on implant therapy success.…”
Section: The Impact Of Glycemic Control On Successful Implant Treatmentmentioning
confidence: 98%
“…That is, to begin to fully and appropriately operationalize implant therapy for medically compromised patients, we will need not only to continue to challenge existing dogma and fully define the long‐term risks, but will also need to understand the benefits gained from implant therapy as an important contribution to improved oral and systemic health . It is perhaps one of the more subtle contributions from these earlier studies challenging the longstanding implications for diabetes in implant therapy that it has taken forward similar considerations across a range of systemic conditions …”
Section: The Impact Of Glycemic Control On Successful Implant Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of advanced age and/or systemic medical conditions on dental implant survival: A systematic review and meta-analysis (Schimmel, Srinivasan, McKenna, Müller, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the placement of standard diameter implants severely resorbed mandibles can be challenging and might necessitate bone augmentation procedures . It has to be considered that advanced surgical procedures are usually accompanied by an element of risk for augmenting biological complications, and more so, especially in the age‐advanced medically compromised patients . Therefore, the adoption of minimally invasive treatment concepts along with surgical procedures that have low morbidities seems a logical alternative.…”
Section: Introductionmentioning
confidence: 99%